If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14m + 9 + -6m = 0 Reorder the terms: 9 + 14m + -6m = 0 Combine like terms: 14m + -6m = 8m 9 + 8m = 0 Solving 9 + 8m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 8m = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 8m = 0 + -9 8m = 0 + -9 Combine like terms: 0 + -9 = -9 8m = -9 Divide each side by '8'. m = -1.125 Simplifying m = -1.125
| 7-3x=(-4)x+13 | | x+12x=30,720.00 | | 0,20=((X*2/100*5)-x) | | 0.05(80)+0.4x=0.2(80+x) | | -9(x+5)=3(x+23) | | x+12x=30,720 | | 3x/10=24/9 | | 3(2)-9=5(2-3) | | 49x^2+168x+144=0 | | -9x-35=3x-69 | | 1=y-2x+5 | | 0.05(80)+0.4=0.2(80+x) | | -9x+-35=3x-69 | | -3(-12+4y)+12y=36 | | 23y-22y-8=-11 | | 14-x=1/2 | | -6=4-(8-z) | | ln(x+4)-2lnx=5 | | 7a-3=2a-20 | | 6x+54=4x+70 | | (2x^2+5x-3)(2x+1)= | | 1-5+(-9)-7-13= | | 28x+13=9x+2 | | f(10)=3x+24 | | 28-12.12=s | | -3x+12y=36 | | 6u^2+3u-84=0 | | c-13=-5 | | x^2(4e^2x)+4x(2e^2x)-18(e^2x)=0 | | 1.8z-0.8z+7.4=-6.6 | | 7v+7.8= | | 0.1=9h |